Hemolytic uremic syndrome: differential diagnosis with the onset of inflammatory bowel diseases - Bianchi, Laura; Gaiani, Federica; Vincenzi, Francesca; Kayali, Stefano; Di Mario, Francesco; Leandro, Gioacchino; de' Angelis, Gian Luigi; Ruberto, Claudio (Acta Biomedica Atenei Parmensis, 2018)
Background: Shiga-toxin Escherichia coli productor (STEC) provokes frequently an important intestinal damage that may be considered in differential diagnosis with the onset of Inflammatory Bowel Disease (IBD). The aim of this work is to review in the current literature about Hemolytic Uremic Syndrome (HUS) and IBD symptoms at the onset, comparing the clinical presentation and symptoms, as the timing of diagnosis and of the correct treatment of both these conditions is a fundamental prognostic factor. A focus is made about the association between typical or atypical HUS and IBD and a possible renal involvement in patient with IBD (IgA-nephropathy). Methods: A systematic review of scientific articles was performed consulting the databases PubMed, Medline, Google Scholar, and consulting most recent textbooks of Pediatric Nephrology. Results: In STEC-associated HUS, that accounts for 90% of cases of HUS in children, the microangiopathic manifestations are usually preceded by gastrointestinal symptoms. Initial presentation may be considered in differential diagnosis with IBD onset. The transverse and ascending colon are the segments most commonly affected, but any area from the esophagus to the perianal area can be involved. The more serious manifestations include severe hemorrhagic colitis, bowel necrosis and perforation, rectal prolapse, peritonitis and intussusception. Severe gastrointestinal involvement may result in life-threatening complications as toxic megacolon and transmural necrosis of the colon with perforation, as in Ulcerative Colitis (UC). Transmural necrosis of the colon may lead to subsequent colonic stricture, as in Crohn Disease (CD). Perianal lesions and strictures are described. In some studies, intestinal biopsies were performed to exclude IBD. Elevation of pancreatic enzymes is common. Liver damage and cholecystitis are other described complications. There is no specific form of therapy for STEC HUS, but appropriate fluid and electrolyte management (better hyperhydration when possible), avoiding antidiarrheal drugs, and possibly avoiding antibiotic therapy, are recommended as the best practice. In atypical HUS (aHUS) gastrointestinal manifestation are rare, but recently a study evidenced that gastrointestinal complications are common in aHUS in presence of factor-H autoantibodies. Some report of patients with IBD and contemporary atypical-HUS were found, both for CD and UC. The authors conclude that deregulation of the alternative complement pathway may manifest in other organs besides the kidney. Finally, searching for STEC-infection, or broadly for Escherichia coli (E. coli) infection, and IBD onset, some reviews suggest a possible role of adherent invasive E. coli (AIEC) on the pathogenesis of IBD. Conclusions: The current literature shows that gastrointestinal complications of HUS are quite exclusive of STEC-associated HUS, whereas aHUS have usually mild or absent intestinal involvement. Severe presentation as toxic megacolon, perforation, ulcerative colitis, peritonitis is similar to IBD at the onset. Moreover, some types of E. coli (AIEC) have been considered a risk factor for IBD. Recent literature on aHUS shows that intestinal complications are more common than described before, particularly for patients with anti-H factor antibodies. Moreover, we found some report of patient with both aHUS and IBD, who benefit from anti-C5 antibodies injection (Eculizumab)